Attributable Fractions of Nonalcoholic Fatty Liver Disease for Mortality in the United States: Results From the Third National Health and Nutrition Examination Survey With 27 Years of Follow‐up. Issue 2 (25th August 2020) - Alvarez, Christian S.; Graubard, Barry I.; Thistle, Jake E.; Petrick, Jessica L.; McGlynn, Katherine A.
Abstract : Background and Aims: Nonalcoholic fatty liver disease (NAFLD) encompasses a range of conditions, from simple steatosis to nonalcoholic steatohepatitis. Studies in the United States have reported an increased mortality risk among individuals with NAFLD; therefore, the population attributable fractions (PAFs) for mortality were examined. Approach and Results: A total of 12, 253 adult individuals with ultrasound assessment of NAFLD from the Third National Health and Nutrition Examination Survey and mortality follow‐up through 2015 were included in the analysis. Cox proportional hazard regression was used to estimate multivariable‐adjusted hazard ratios (HRs) and 95% confidence intervals (CIs) for NAFLD in association with all‐cause and cause‐specific mortality. Overall, sex‐ and race/ethnicity‐specific PAFs and 95% CIs were estimated. In the current study, presence of NAFLD was associated with a 20% increased risk of all‐cause mortality (HR, 1.20; 95% CI, 1.08, 1.34). The overall PAF for all‐cause mortality associated with NAFLD was 7.5% (95% CI, 3.0, 12.0). The PAF for diabetes‐specific mortality was 38.0% (95% CI, 13.1, 63.0) overall, 40.8% (95% CI, 2.1, 79.6) in men, and 36.8% (95% CI, 6.6, 67.0) in women. The PAF for liver disease (LD)‐specific mortality was notably higher in men (68.3%; 95% CI, 36.3, 100.0) than women (3.5%; 95% CI, −39.7, 46.8). In the race‐specific analysis, the PAFs of NAFLD for all‐cause mortality (9.3%; 95% CI, 4.0, 14.6) and diabetes‐specific mortality (44.4%; 95% CI, 10.8, 78.0) were significantly greater than zero only for whites. Conclusions: In the United States, approximately 8% of all‐cause mortality and more than one‐third of LD‐ and diabetes‐specific deaths are associated with NAFLD. With these high percentages, efforts are needed to reduce the burden of NAFLD in the United States.